OECDscience technology and industry scoreboard 2011 / Innovation and growth in knowledge economies (Paris : OECD publishing, 2011)
This tenth edition of the OECD Science, Technology and Industry (STI) Scoreboard builds on the OECD's 50 years of indicator development to present major world trends in knowledge and innovation. It analyses a wide set of indicators of science, technology, globalisation and industrial performance in OECD and major non-OECD countries (notably Brazil, the Russian Federation, India, Indonesia, China and South Africa) and includes some experimental indicators that provide insight into new areas of policy interest.
Chapter 1. Knowledge economies: Trends and features - Chapter 2. Building Knowledge - Chapter 3. Conneting to knowledge - Chapter 4. Targeting new growth areas - Chapter 5. Uleashing innovation in firms - Chapter 6. Competing in the global economy.
Keywords: Tecnologia - Industria - Scienza